Teaching expressive reading as one of the methods of conscious learning - Ilsoyar Aftahovna Sadykova, Aliya Nailevna Miftakhova,; Vasilevna Iliasova, Svetlana (Opción, 2019)
The study aims to investigate teaching expressive reading as one of the methods of conscious learning via comparative qualitative research methods. As a result, expressive reading is a means of effective control of the understanding and mastering of the language. The authors of the article drew conclusions that expressive reading contributed to a more conscious adoption of the rules of syntax and punctuation of the Russian language, the development of verbal hearing, and therefore the solution of the most important task in teaching the Russian language as a foreign language.